Encyclopedia of Automotive Engineering 2014
DOI: 10.1002/9781118354179.auto143
|View full text |Cite
|
Sign up to set email alerts
|

Trends—Spark Ignition

Abstract: Current and future combustion engine development targets a considerable reduction in fuel consumption and emissions to meet strict emission legislation despite steady or increasing customer comfort and performance demands. Additionally, reduced time to market is required despite increasing variations in customer demands and fuel qualities in worldwide markets. To meet these targets, gasoline engines have made progress in efficiency by the introduction of technologies such as direct injection in combination wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…A similar trend is observed in the location of the efficiency peak, which, for the axial type, is shifted to even lower Blade Speed Ratio (BSR) [9]. For the sake of completeness, it is worth mentioning that, in spite of the above-mentioned pros, radial turbines for automotive turbocharging size exhibit a higher efficiency peak, as well as a wider BSR area where these values are attained [9]. Early studies on axial-flow turbine turbochargers showed very promising results, such as those conducted by Honeywell on the "Dual Boost concept", in which a double sided compressor is coupled with an axial turbine [10].…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…A similar trend is observed in the location of the efficiency peak, which, for the axial type, is shifted to even lower Blade Speed Ratio (BSR) [9]. For the sake of completeness, it is worth mentioning that, in spite of the above-mentioned pros, radial turbines for automotive turbocharging size exhibit a higher efficiency peak, as well as a wider BSR area where these values are attained [9]. Early studies on axial-flow turbine turbochargers showed very promising results, such as those conducted by Honeywell on the "Dual Boost concept", in which a double sided compressor is coupled with an axial turbine [10].…”
Section: Introductionsupporting
confidence: 68%
“…Similar considerations to those concerning mixed-flow turbines swallowing capacity have led, only recently, to investigate the suitability of axial-flow turbines in turbocharging applications as well. In fact, at the same design mass flow rate, passing from radial to mixed-flow and to axial-turbines rotor inertia is progressively lowered [9]. A similar trend is observed in the location of the efficiency peak, which, for the axial type, is shifted to even lower Blade Speed Ratio (BSR) [9].…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation